The potential for desalination in India. (20th November 2007) - Tewari, P.K.
The demand for water in India is increasing rapidly owing to progressive increase in the use of water for irrigation, rapid industrialisation, population growth and improving life standards. A holistic approach is therefore required to cope with the freshwater needs of the country. It includes: seawater desalination in coastal areas; brackish water desalination; water purification; water reuse; rainwater harvesting; water supply schemes. The contribution of seawater and brackish water desalination would play an important role in augmenting the freshwater needs of the country.